2008
DOI: 10.1007/s10804-008-9046-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Generativity in Psychological Well-Being: Does it Differ for Childless Adults and Parents?

Abstract: Given that parenthood is considered a central adult status with developmental implications, and an increasing number of adults are childless, we assessed whether adult development is structured differently for parents and non-parents. This study's main goal was to assess and compare the connection between generativity development-a key task of middle adulthood-and psychological well-being for childless adults (N = 289) and parents (N = 2,218), ages 35-74, using the 1995 MIDUS dataset. We also examined differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 52 publications
(75 reference statements)
0
65
1
5
Order By: Relevance
“…In this study, a slightly higher mean score of generative concern in Sri Lankan elders, compared to such figures in elders in other countries was observed (14,16,21). The findings also indicate that gender and age are not related to generative concern.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…In this study, a slightly higher mean score of generative concern in Sri Lankan elders, compared to such figures in elders in other countries was observed (14,16,21). The findings also indicate that gender and age are not related to generative concern.…”
Section: Discussioncontrasting
confidence: 48%
“…In general, it is found that generative concern is positively associated with psychological well-being (14,15). Further investigations, however, are needed to validate the LGS in this target population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations